2021
DOI: 10.1002/biof.1782
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutics studies and biological properties of Teucrium polium (Lamiaceae)

Abstract: Teucrium polium has been used in traditional medicine as antifungal, antipyretic, antispasmodic, and antibacterial. It is consumed by many jordanians for the treatment of many diseases. The effects of this plant have been investigated in kidney, liver, and brain. Its antidiabetic, antimicrobial, antioxidant, and anticancer effects have been introduced. Polyphenolic compound, flavonoids, monoterpenes, alkanoides, and essential oils were identified. Several studies revealed that this plant has a hypoglycemic eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 88 publications
(83 reference statements)
1
6
0
Order By: Relevance
“…Free access was given to both food and water. Dose, duration and route of treatment were selected according to previous published reports in rats and ethno-pharmacological studies [ 7 , 8 , 12 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Free access was given to both food and water. Dose, duration and route of treatment were selected according to previous published reports in rats and ethno-pharmacological studies [ 7 , 8 , 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…It is also commonly used for antibacterial, antispasmodic, antiulcer, anorexic, and antipyretic agents and has a hepato-protective activity against CCl 4 induced hepato-oxidative stress in rats [ 10 , 11 ]. It has been reported that extracts of T. polium are rich in phenolic compounds, which allow them to possess hepato-protection via the inhibition of lipoperoxidation and enhancing the activity of antioxidant enzymes [ 12 ]. Recently, using high resolution-liquid chromatography mass spectroscopy (HR-LCMS), it was reported that T. polium dominant compounds include several small peptides associated (1) 13R-hydroxy-9E,11Z-octadecadienoic acid, (2) Rhoifolin, (3) Sericetin diacetate, (4) Selinidin, (5) Valtratum, (6) Triptonide, (7) Koparin 2′-Methyl Ether, (8) Dihydrosamidin, (9) 4, 16alpha, 17beta-Estriol 3-(beta-Dglucuronide), (10) Cepharanthine, (11) Carapin-8 (9)-Ene, (12) 1-dodecanoyl-sn-glycerol [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical screening of the TP crude extract showed the presence of flavonoids, phenolics, and alkaloid compounds. These bioactive compounds make TP a potent candidate for potential pharmaceutical use to promote human health [ 8 , 23 , 24 ]. Several studies have demonstrated that flavonoids have anti-inflammatory properties in acute and chronic inflammation [ 8 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, precaution should be taken with the use of TP for prolonged periods of time. High doses (200 mg/kg) of TP for 28 days have been reported to exhibit toxic effects on different organs, such as the kidney and liver [ 24 ]. The effects of the crude extract of TP cannot be attributed to a single phytochemical moiety [ 8 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Owing to its remarkable pharmaco-logical properties, it has been considered a widely used herbaceous plant in folk medicine for over 2000 years. It has anti-inflammatory, antibacterial, antitumor, hepatoprotective and hypoglycemic activities (Rahmouni et al, 2021), in addition to diuretic, tonic, antirheumatic, antifungal, antispasmodic and antipyretic properties. Its main constituents include asparagine, ditryne, β-caryophyllene, diterpenoids, flavonoids, saponins, terpenoids and sterol (Khazaei et al, 2018).…”
Section: Introductionmentioning
confidence: 99%